Is There Any Synchronism Between the Business Cycles of Argentina and Brazil? Existe alguma sincronização entre os ciclos econômicos da Argentina e do Brasil? - Jacobo, Alejandro Damián; Clavero, Lautaro (Revista de Economia, 2025)
This paper explores the behavior of business fluctuations in Argentina and Brazil over the last quarter-century. Argentina exhibits greater volatility, with its economic fluctuations being two and a half times more intense than those of Brazil. Although the concordance between both economies is 60%, the countries are weakly correlated. Argentina’s contemporary GDP is influenced by and retains information from two previous quarters. As for the components of GDP, Consumption and Gross Capital Investment are more volatile in Argentina. The Trade Balance exhibits low relative volatility and plays a countercyclical role in both countries. Although the economies show some interesting parallel variations, remaining simultaneously in the same phase of the economic cycle, the volatility of one of the main economies, together with the weak correlation of business fluctuations, suggests that the successful application of homogeneous macroeconomic policies is still distant.